Electromagnetic wave absorber, system equipped with electromagnetic wave absorber, and method for absorbing electromagnetic waves using electromagnetic wave absorber
The electromagnetic wave absorber utilizing Mie resonance in dielectric materials addresses the limitations of conventional absorbers by achieving high-frequency absorption in electronic devices, enhancing electromagnetic interference mitigation.
Patent Information
- Application Number
- JP2021028921
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-02-25
AI Technical Summary
Conventional magnetic electromagnetic wave absorbers face limitations in maintaining high absorption characteristics in the high frequency range due to Snoek's limit, and there are no effective applications of dielectric metamaterials for electromagnetic interference mitigation in electronic devices beyond optical components.
An electromagnetic wave absorber utilizing magnetic loss based on Mie resonance of dielectric materials, composed of a dielectric arrangement group with disc-shaped dielectrics, optimized for high permittivity, thickness, and spacing to enhance absorption across high frequencies.
The absorber effectively absorbs electromagnetic waves in the GHz band with high magnetic loss, providing superior absorption characteristics independent of incident angle and frequency, suitable for electronic devices and systems.
Smart Images

Figure 0007600750000046 
Figure 0007600750000047 
Figure 0007600750000048
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave absorber, a system including the electromagnetic wave absorber, and a method for absorbing electromagnetic waves using the electromagnetic wave absorber. [Background technology]
[0002] Metamaterials are artificial materials whose size is smaller than the wavelength of the electromagnetic waves they target, and have attracted attention in recent years because they exhibit properties not found in natural materials. In particular, materials called left-handed metamaterials exhibit a negative refractive index in a specific frequency range. For this reason, research and development of these materials is being actively conducted with the aim of applying them to new optical applications such as perfect lenses and invisibility cloaks.
[0003] In 1999, British physicist J.B. Pendry proposed a nanometal structure with a periodic structure smaller than the wavelength of electromagnetic waves, and theoretically demonstrated that the refractive index of this structure is negative (Non-Patent Document 1). This nanometal structure has a structure in which nanounits consisting of tiny split ring resonators (SRRs) and metal wires are arranged three-dimensionally. By reducing the size of the nanounits, the nanometal structure acts as a homogeneous medium for electromagnetic waves and exhibits electromagnetic wave response that depends on the functions of the SRRs and metal wires. The SRRs act as LC resonators for electromagnetic waves and exhibit negative permeability above the resonant frequency. In addition, conductive metal wires exhibit negative dielectric constants. By combining SRRs and metal wires, both the effective dielectric constant and effective permeability become negative, and as a result, the refractive index, which is expressed as the product of the square root of the dielectric constant and the square root of the permeability, becomes negative. Furthermore, Pendry theoretically demonstrated that by using left-handed metamaterials that exhibit a negative refractive index, it is possible to realize a perfect lens that can observe structures as fine as possible, exceeding the diffraction limit of light (Non-Patent Document 2).
[0004] Following Pendry's announcement, American physicist DR Smith and his colleagues actually fabricated a nanometal structure consisting of SRRs and metal wires, and demonstrated that the permittivity and permeability of this structure become negative in the microwave region (Non-Patent Document 3). Following these announcements, metamaterials suddenly began to attract attention.
[0005] On the other hand, dielectric metamaterials that use dielectrics instead of nanometal structures have been proposed. Nanometal structures have the disadvantages of large conductor loss and the need for precision and fine processing technology for their manufacture. In contrast, dielectric metamaterials have the advantages of small loss during non-resonance and being easy to manufacture.
[0006] For example, R. Yahiaoui et al. have proposed a structure in which dielectric resonators made of high-permittivity TiO2 ceramic disks are periodically arranged two-dimensionally (Non-Patent Document 4). When the size of the dielectric resonator is reduced to approximately the wavelength of the electromagnetic wave, Mie resonance occurs. Therefore, it becomes possible to use either the TE resonance or the TM resonance mode. In the TE resonance mode, the dielectric resonator exhibits a negative effective permeability above the resonance frequency. Also, in the TM resonance mode, it exhibits a negative effective permittivity above the resonance frequency. In this respect, it can be said that the TE resonance mode corresponds to the SRR of a nanometal structure, and the TM resonance mode corresponds to a metal wire. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] JBPendry et al., Magnetism from Conductors, and Enhanced Non-linear Phenomena, IEEE Transactions on Microwave Theory and Techniques, November 1999, volume 47, Issue 11, pages 2075-2084 [Non-Patent Document 2] JBPendry, Negative Refraction Makes a Perfect Lens, PYSICAL REVIEW LETTERS, 30 October, 2000, Volume 85, Number 18, page 3966-3969 [Non-Patent Document 3] RASHelby et al, Experimental Verification of a Negative Index of Refraction, Science, 6 April, 2001, Volume 292, Issue 5514, pages 77-79 [Non-Patent Document 4] R.Yahiaoui et al., Towards left-handed metamaterials using single-size dielectric resonators: The case of TiO2-disks at millimeter wavelengths, APPLIED PHYSICS LETTERS, Volume 101, 042909 (2012) Summary of the Invention [Problem to be solved by the invention]
[0008] Thus, although there has been active development of metamaterials such as dielectric metamaterials, most of these studies have focused on materials that exhibit a negative refractive index, i.e., left-handed metamaterials, and aim for optical applications such as perfect lenses, transparency cloaks, etc. Although there are a few known technologies for applying nanometal structures to antennas and transmission lines in the microwave region, there are no known technologies aimed at applying dielectric metamaterials to electronic devices other than optical components.
[0009] On the other hand, with the rapid development of electronic, information and communication technology in recent years, the use of electromagnetic waves has rapidly increased, and the electromagnetic waves used are becoming higher in frequency and wider in bandwidth. As the use of electromagnetic waves expands and the frequency increases, electromagnetic interference issues, such as malfunction of electronic devices and adverse effects on the body due to electromagnetic noise, have come to the forefront, and there is an increasing demand for EMC measures.
[0010] As one method of EMC countermeasures, a method has been proposed in which electromagnetic wave absorbers (radio wave absorbers) are used to absorb unnecessary electromagnetic waves and prevent their intrusion. Electromagnetic wave absorbers utilize the phenomenon (absorption attenuation) in which the absorber absorbs the energy of incident electromagnetic waves (electromagnetic wave energy), converts it to thermal energy, and radiates it. To effectively utilize absorption attenuation, it is important to use an absorber (absorption material) that exhibits excellent absorption characteristics. Specifically, it is desirable for the absorber's transmission attenuation (rate) to be high in the absorption band.
[0011] Electromagnetic wave absorption utilizes the magnetic loss, dielectric loss, or resistance loss of the material that constitutes the absorber, and absorbers that utilize these losses are called magnetic electromagnetic wave absorbers, dielectric electromagnetic wave absorbers, and resistive electromagnetic wave absorbers, respectively. Of these, magnetic electromagnetic wave absorbers that use ferromagnetic materials such as soft magnetic metal powder and ferrite powder are widely used because they exhibit excellent absorption characteristics.
[0012] Magnetic electromagnetic wave absorbers utilize the loss that occurs due to the magnetic resonance of ferromagnetic materials. That is, ferromagnetic materials have a magnetic moment based on the spin angular momentum of electrons (3d electrons) that are mainly bound to magnetic elements (Fe, Ni, Co, etc.). In addition, due to interactions, the direction of each magnetic moment is bound, resulting in spontaneous magnetization. When electromagnetic waves are irradiated to a magnetic material, the direction of magnetization fluctuates due to domain wall movement in the low frequency range and due to magnetization rotation in the high frequency range. As the frequency increases, the magnetization fluctuation interferes with the electromagnetic wave at a specific frequency, resulting in a phenomenon in which the magnetization resonates, that is, magnetic resonance. At the frequency at which magnetic resonance occurs, the imaginary part of the magnetic permeability (μ'') peaks and the loss becomes maximum. Loss due to magnetic resonance is called magnetic loss.
[0013] However, there is still room for improvement in magnetic electromagnetic wave absorbers proposed so far. That is, magnetic electromagnetic wave absorbers absorb electromagnetic waves by utilizing the magnetic loss of ferromagnetic materials. On the other hand, a theory called Snoek's limit is known regarding magnetism, and according to this theory, there is a relationship between the upper limit of magnetic permeability of a magnetic material and the resonance frequency. Therefore, it is difficult to maintain high magnetic permeability in the high frequency range, and therefore there is a limit to obtaining excellent electromagnetic wave absorption characteristics in the high frequency range.
[0014] The present inventors have conducted extensive research in light of the above circumstances, and have found that even in a dielectric material that does not contain a magnetic element, if its characteristics and shape are controlled, a Mie resonance mode is generated and magnetic resonance occurs, and that if this magnetic resonance is utilized, an electromagnetic wave can be made to penetrate into the absorber by controlling the thickness of the dielectric material, resulting in the absorption of the electromagnetic wave.
[0015] The present invention has been completed based on such findings, and an object of the present invention is to provide an electromagnetic wave absorber that utilizes magnetic loss based on Mie resonance of a dielectric, a system including this electromagnetic wave absorber, and a method for absorbing electromagnetic waves using this electromagnetic wave absorber. [Means for solving the problem]
[0016] The present invention includes the following aspects (A) to (J). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."
[0017] (A) a substrate and a dielectric arrangement group composed of a plurality of disk-shaped dielectrics; Each of the dielectric bodies constituting the dielectric body arrangement group has a front surface and a bottom surface, and is arranged so that the bottom surface faces one surface of the base body; The dielectrics constituting the dielectric arrangement group have a relative dielectric constant real part ε r ' is 30 or more, average diameter D m is 100μm or more and 10,000μm or less (0.1mm or more and 10mm or less), average thickness T mis 20μm or more and 300μm or less (0.02mm or more and 0.3mm or less), and the average thickness T m Average diameter D m Ratio of (D m / T m The electromagnetic wave absorber has a thickness T ratio of 3 or more and a coefficient of variation CV of the thickness T of 20% or less.
[0018] (B) The electromagnetic wave absorber of (A) above, wherein the area ratio of the dielectrics constituting the dielectric arrangement group is 10% or more and 90% or less.
[0019] (C) the surface density of the dielectrics constituting the dielectric arrangement group is 3 pieces / cm 2 The electromagnetic wave absorber according to the above (A) or (B).
[0020] (D) The electromagnetic wave absorber according to any one of (A) to (C) above, wherein the dielectric tangent (tan δ) of the dielectrics constituting the dielectric arrangement group is 0.03 or more.
[0021] (E) The electromagnetic wave absorber according to any one of the above (A) to (D), wherein the dielectric is a dried body, a molded body or a sintered body of a dielectric material.
[0022] (F) A system comprising an electromagnetic wave radiation source and any one of the electromagnetic wave absorbers (A) to (E) above, The frequency f (unit: Hz) of the electromagnetic wave radiated by the electromagnetic wave radiation source and the real part ε of the relative dielectric constant of the dielectric r ', the average diameter D m (unit: μm) and the thickness T m (unit: μm) and are expressed by the following formulas (1) to (4) (where c is the speed of light (3.0 × 10 14 A system that satisfies the above requirements.
number
number
number
number
[0023] (G) The system of (F) above, wherein the electromagnetic radiation source is a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable.
[0024] (H) The system according to (F) or (G) above, wherein the absolute value of the return loss of the electromagnetic wave absorber at the frequency f is 10 dB or more.
[0025] (I) A method for absorbing electromagnetic waves using any one of the electromagnetic wave absorbers (A) to (E) above, The frequency f of the electromagnetic wave (unit: Hz) and the real part of the relative dielectric constant ε r ', the average diameter D m (unit: μm) and the average thickness T m (unit: μm) and are expressed by the following formulas (1) to (4) (where c is the speed of light (3.0 × 10 14 A method for satisfying the above requirement.
number
number
number
number
[0026] (J) The method according to (I) above, wherein the electromagnetic waves are leakage electromagnetic waves from a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable.
[0027] (K) The method according to (I) or (J) above, wherein the absolute value of the return loss of the electromagnetic wave absorber at the frequency f is 10 dB or more. Effect of the Invention
[0028] According to the present invention, there are provided an electromagnetic wave absorber that utilizes magnetic loss based on Mie resonance of a dielectric, a system including this electromagnetic wave absorber, and a method for absorbing electromagnetic waves using this electromagnetic wave absorber. [Brief description of the drawings]
[0029] [Figure 1] 4 shows the frequency dispersion of the complex relative dielectric constant of the electromagnetic wave absorber obtained in Example 1. [Diagram 2] 4 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 1. [Diagram 3] 4 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 2. [Figure 4] 1 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 3. [Diagram 5] 1 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 4. [Figure 6] 13 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 5. [Figure 7] 13 shows the frequency dispersion of the complex relative permeability of the electromagnetic wave absorber obtained in Example 6. [Figure 8] The electromagnetic wave absorbing characteristics of the electromagnetic wave absorber obtained in Example 1 are shown below. [Figure 9] The electromagnetic wave absorbing characteristics of the electromagnetic wave absorber obtained in Example 2 are shown below. [Figure 10] The electromagnetic wave absorption characteristics of the electromagnetic wave absorber obtained in Example 3 are shown below. [Figure 11] The electromagnetic wave absorption characteristics of the electromagnetic wave absorber obtained in Example 4 are shown below. [Figure 12] The electromagnetic wave absorption characteristics of the electromagnetic wave absorber obtained in Example 5 are shown below. [Figure 13] The electromagnetic wave absorption characteristics of the electromagnetic wave absorber obtained in Example 6 are shown below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] 1.Electromagnetic wave absorber The electromagnetic wave absorber of this embodiment includes a base and a dielectric arrangement group. This dielectric arrangement group is composed of a plurality of disk-shaped dielectrics. Each of the dielectrics constituting this dielectric arrangement group has a front surface and a bottom surface, and is arranged so that the bottom surface faces one surface of the base. Furthermore, the dielectrics constituting this dielectric arrangement group have a relative dielectric constant real part ε r ' is 30 or more, average diameter D m is 100μm or more and 10000μm or less (0.1mm or more and 10mm or less), and the average thickness T m The average thickness T m Average diameter D m Ratio of (D m / T m The ratio) is 3 or more, and the coefficient of variation CV of the thickness T is 20% or less.
[0031] The electromagnetic wave absorber of this embodiment includes a disk-shaped dielectric (hereinafter, sometimes referred to as "dielectric"). This dielectric acts as a dielectric metamaterial and exhibits a resonance mode known as Mie resonance. Therefore, it exhibits magnetic loss based on magnetic resonance in a predetermined frequency range and exhibits electromagnetic wave absorption characteristics in this frequency range.
[0032] First, a general theory on Mie resonance will be explained. When the size of a dielectric is comparable to or smaller than the wavelength of the incident electromagnetic wave, a steady state of electric and magnetic fields is generated inside the dielectric at a certain frequency (the first Mie resonance frequency), which causes the resonance phenomenon to occur. This resonance phenomenon is called Mie resonance. To explain in more detail, when the electromagnetic wave radiation source is in the far field, the electromagnetic wave is incident on the dielectric as a plane wave. At this time, the electromagnetic wave is incident so that both the tangential and perpendicular components of the electromagnetic wave electric field component satisfy the boundary conditions at the interface between the dielectric and air. As a result, an electromagnetic field distribution different from that of the previous propagation medium occurs inside the dielectric. Among these, in the mode corresponding to magnetic Mie resonance, a vortex-like distribution of electric field and displacement current occurs inside the dielectric.
[0033] As a result of the generation of a vortex-shaped displacement current (electric field) inside the dielectric, an oscillating magnetic field is generated inside the dielectric perpendicular to the displacement current (electric field). In this regard, the vortex-shaped displacement current (electric field) distribution inside the dielectric can be considered as a magnetic dipole. This oscillating magnetic dipole interacts with the magnetic field component of the incident electromagnetic wave, causing magnetic resonance at a specific frequency (first Mie resonance frequency). In short, the electric field component of the incident electromagnetic wave creates a magnetic dipole inside the dielectric, and magnetic resonance occurs when this magnetic dipole interacts with the electromagnetic wave magnetic field component.
[0034] Similarly, electrical resonance occurs. That is, the magnetic field component of the incident electromagnetic wave generates an electric dipole in the dielectric, and this electric dipole and the electromagnetic wave electric field component resonate electrically at a specific frequency (second Mie resonance frequency).
[0035] The inventors' investigations revealed that magnetic resonance based on Mie resonance generates magnetic loss, and that the magnitude of the magnetic loss is large enough to absorb electromagnetic waves. In other words, the inventors have calculated the effective dielectric constant (ε eff ) and effective permeability (μ eff ) and then calculate the magnetic loss (Q M ) was estimated.
[0036] Here, the Lewin model is a model that theoretically considers the electromagnetic wave response of a composite in which a large number of spherical particles (particle size a, dielectric constant ε2, magnetic permeability ε2) are dispersed in a matrix (dielectric constant ε1, magnetic permeability μ1) while maintaining a periodic interval p. The effective dielectric constant of the composite (ε eff ) and effective permeability (μ eff ) can be calculated according to the following formulas (5) to (7). In addition, the magnetic loss (Q M ) can be calculated according to the sum rule shown in the following formula (8). In the following formulas (5) to (8), v is the volume fraction of the spherical particles in the matrix, f is the frequency, ω is the angular frequency, and c is the speed of light. Also, μ'' is the effective permeability μ eff is the imaginary part of
[0037]
number
number
number
number
[0038] Using the above equations (5) to (8), the magnetic loss (Q M ) was obtained, and it was found that even when the spherical particles and matrix do not have magnetic components (magnetic elements), that is, when μ1 = μ2 = 1, the magnetic loss (Q M ) was found to occur. In addition, this magnetic loss (Q M ) was found to be highly dependent on the dielectric constants (ε1, ε2) of the spherical particles and the matrix. Furthermore, as the frequency (f) of the electromagnetic wave increases, the magnetic loss (Q M ) was found to increase sharply.
[0039] It was thus found that the use of a dielectric with a high dielectric constant generates large magnetic loss due to Mie resonance in the high frequency range, and it is expected that this magnetic loss can be applied to electromagnetic wave absorption.
[0040] Next, the electromagnetic wave absorber of this embodiment will be described. The electromagnetic wave absorber of this embodiment includes a base. The base has a function of holding a dielectric, and the material is not limited as long as it has this function. Examples of the base include resin, metal, and ceramics. The shape is also not limited, and examples of the shape include a plate, sheet, and foil. By using a sheet-shaped resin base or a foil-shaped metal base, it is possible to impart flexibility to the electromagnetic wave absorber. Furthermore, by using a metal base, the base can be given the function of an electromagnetic wave reflecting layer.
[0041] The electromagnetic wave absorber of this embodiment includes a dielectric arrangement group consisting of a plurality of disk-shaped dielectrics in addition to the base. Each of the dielectrics constituting the dielectric arrangement group has a front surface and a bottom surface, and is arranged so that the bottom surface faces one surface of the base. That is, the disk-shaped dielectrics are distributed on the base so that the bottom surface is approximately parallel to the surface of the base. By distributing the disk-shaped dielectrics, it becomes possible to efficiently absorb electromagnetic waves. That is, a part of the electromagnetic waves is reflected by the surface of the dielectric. Therefore, not all of the incident electromagnetic waves penetrate into the dielectric and are attenuated. For example, if the dielectric is uniformly formed on the base, the proportion of electromagnetic waves reflected by the surface of the dielectric increases, and there is a risk of the absorption characteristics being reduced. In contrast, when a plurality of disk-shaped dielectrics are arranged, gaps are formed between the dielectrics, and electromagnetic waves penetrate into these gaps due to phenomena such as diffraction. The electromagnetic waves that penetrate into the gaps resonate with the dielectric, causing absorption. The gaps may be easily penetrated by electromagnetic waves, and may be, for example, a resin or an air layer. If penetration is easy, an absorbing material such as a conductive material may be contained in the gaps.
[0042] Each dielectric included in the electromagnetic wave absorber of this embodiment has a disk shape. That is, the cross section is circular. It is preferable that the cross section of the dielectric is as close to a perfect circle as possible. A perfect circle has a constant diameter. However, it may be difficult to manufacture a dielectric with a perfectly circular cross section. Therefore, the dielectric is not limited to a perfectly circular cross section. For each dielectric, a variation in diameter of ±10% or less is acceptable.
[0043] In addition, in the electromagnetic wave absorber of this embodiment, it is preferable that the variation in size (diameter) between the dielectrics included in the dielectric arrangement group is as small as possible. If the dielectric sizes (diameters) vary, the resonance frequencies of the respective dielectrics will not be uniform, which may make it difficult to obtain steep and deep electromagnetic wave absorption characteristics. The variation in the diameters of the dielectrics is preferably ±10% or less.
[0044] The dielectrics included in the dielectric arrangement group may be arranged regularly or irregularly. Furthermore, the number of dielectrics may be two or more. The gaps between the dielectrics may be filled with a material such as resin, or may not be filled. By arranging the dielectrics in this manner, the electromagnetic waves incident from the absorber surface efficiently penetrate into the dielectrics and are absorbed therein.
[0045] The dielectric is not limited to a specific material as long as it is made of a high dielectric constant material. For example, barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), bismuth alkali titanate (BiTiO3), etc. 0.5 K 0.5 TiO3, Bi 0.5 Na 0.5 Examples of high dielectric constant materials include high-dielectric constant materials such as TiO3, alkali niobate (NaNbO3, KNbO3, etc.), lead-based materials (PZT, PMN-PT, etc.), and bismuth layered compounds (SBT, etc.). The dielectric may contain only one of these materials, or may contain multiple materials. When multiple materials are contained, they may be contained in the form of a mixed crystal or a solid solution. The dielectric may be barium titanate (BaTiO3) and bismuth potassium titanate (Bi 0.5 K 0.5 TiO3).
[0046] The dielectric may be polycrystalline or single crystalline. The dielectric may be a dried, molded or sintered body of the dielectric material. The dried body is a dielectric material that is dried to remove liquid components such as organic solvents, and the molded body is a dielectric material that is molded. The sintered body is a molded body that is sintered. There is a concern that some of the solvent may remain in the dried body. Therefore, it is preferable for the solvent to have a low boiling point so that it is less likely to remain. It is also preferable for the solvent to have a high dielectric constant so that problems are less likely to occur even if it remains. However, since the dispersion of the powder in the paste is also important, the solvent may be selected while taking into consideration the balance with dispersibility. The same applies to the dispersant.
[0047] The dielectric may be produced by a known method. For example, a dielectric that is a ceramic sintered body may be produced by molding and firing a dielectric raw material. The dielectric raw material may be synthesized by a known method such as a solid-phase reaction method, a complex polymerization method, a coprecipitation method, a hydrothermal synthesis method, a sol-gel method, and a gas phase method. In addition to the dielectric raw material, additives such as a molding aid and a sintering aid may be added. A dielectric that is a single crystal may be produced by a known method such as an aqueous solution method, a hydrothermal synthesis method, a flux method, a Bernoulli method, a Czochralski method, a Bridgman method, a floating zone melting method, a skymelt method, a sublimation recrystallization method, a chemical transport method, and a chemical vapor deposition method.
[0048] In the electromagnetic wave absorber of the present embodiment, each of the dielectrics constituting the dielectric arrangement group has a relative dielectric constant real part ε r ε' is 30 or more. By using a high dielectric constant dielectric, it is possible to impart high electromagnetic wave absorbing performance to an electromagnetic wave absorber comprising this dielectric. In other words, the higher the dielectric constant of the dielectric, the greater the effect of shortening the wavelength of electromagnetic waves due to the increase in the refractive index, and Mie resonance can be realized with a smaller absorber. The higher the dielectric constant of the dielectric, the more preferable it is. ε r is preferably 100 or more, and more preferably 300 or more. r The upper limit of ' is not particularly limited, but is typically 2000 or less, more typically 1000 or less. The reason why the measurement frequency is set to 100 MHz is that there are problems with the measurement technique in the frequency range above GHz, making it difficult to accurately measure the dielectric constant of a high dielectric constant material.
[0049] The dielectrics constituting the dielectric arrangement group have an average thickness T m is 20 μm or more and 300 μm or less (0.02 mm or more and 0.3 mm or less). Here, the average thickness refers to the average value of the thicknesses T of the multiple dielectrics that make up the dielectric arrangement group. To explain this point, it is known that a material in Mie resonance behaves similarly to Fabry-Perot resonance. In addition, in Fabry-Perot resonance, the thickness d' of a material is R ' and resonant frequency f RIt is known that the relationship shown in the following formula (9) is satisfied. In the following formula (9), c is the speed of light, and ε' is the real part of the relative dielectric constant of the material.
[0050]
number
[0051] From the results of Fabry-Perot resonance, it can be inferred that in Mie resonance, the condition that the thickness d of the dielectric satisfies the above equation (9), that is, the thickness T of the dielectric is half the resonant wavelength (λ R It is expected that magnetic losses will be large under conditions close to 0.05 mm / s.
[0052] From this, it can be inferred that the average thickness of the dielectric T m By limiting the average thickness T, it is possible to effectively utilize the magnetic loss due to Mie resonance in the frequency range of, for example, 30 GHz to 1 THz, and as a result, it is possible to fully exhibit the electromagnetic wave absorption characteristics. m may be 30 μm or more and 250 μm or less, 50 μm or more and 200 μm or less, or 70 μm or more and 150 μm or less.
[0053] The dielectrics constituting the dielectric arrangement group have an average diameter D m is 100 μm or more and 10,000 μm or less (0.1 mm or more and 10 mm or less). The inventors have found through their research that the efficiency of electromagnetic wave absorption can be maximized by making the diameter of the disk-shaped dielectric smaller than the wavelength of the incident electromagnetic wave. That is, as mentioned above, by arranging multiple disk-shaped dielectrics, gaps are created between the dielectrics. The electromagnetic waves penetrate into these gaps, and electromagnetic wave absorption is carried out efficiently. By making the diameter of the dielectric smaller than the wavelength of the incident electromagnetic wave, the penetration of the electromagnetic waves into the gaps between the dielectrics is promoted, and as a result, the resonance phenomenon of the dielectric occurs more significantly. Average diameter D m may be 200 μm or more and 5000 μm or less, 300 μm or more and 3000 μm or less, or 500 μm or more and 2000 μm or less.
[0054] The dielectrics constituting the dielectric arrangement group have an average thickness T m Average diameter D m Ratio of (D m / T m The ratio of the dielectric loss to the absorber is 3 or more. As a result of the inventor's repeated investigations, it was found that a flat dielectric material can realize a thinner absorber. That is, D m / T m By increasing the aspect ratio, Mie resonance occurs at a lower frequency than when the thickness is the same. In other words, if the Mie resonance frequency is the same, a thinner absorber can be realized. m / T m A ratio of 5 or more is preferred, and a ratio of 10 or more is even more preferred.
[0055] The dielectric arrangement group has a coefficient of variation CV of the thickness T of the dielectrics constituting the dielectric arrangement group of 20% or less. Here, the coefficient of variation CV is an index of variation. In other words, by reducing the variation in thickness between the dielectrics constituting the dielectric arrangement group, the resonance frequencies of the respective dielectrics are made uniform. As a result, it is possible to obtain steeper and deeper electromagnetic wave absorption characteristics. The coefficient of variation is preferably 15% or less, and more preferably 10% or less. The coefficient of variation CV is the coefficient of variation of the thickness T of each of the dielectrics constituting the dielectric arrangement group. i and the average thickness T m It is calculated according to the following formulas (10) and (11) using the above formulas. In the following formulas (10) and (11), n is the number of dielectrics constituting the dielectric arrangement group, u 2 is the unbiased variance (sample variance) of thickness, and u is the sample standard deviation of thickness.
[0056]
number
number
[0057] Preferably, the area ratio of the dielectrics constituting the dielectric arrangement group is 10% or more and 90% or less. Here, the area ratio of the dielectrics refers to the ratio of the total area of the front surface (or bottom surface) of the dielectrics to the total area of the region on the surface of the base where the dielectrics are dispersed. That is, it refers to the ratio of the area occupied by the dielectrics when the electromagnetic wave absorber is viewed from above. When the area ratio is 10% or more, the ratio of the dielectrics that cause magnetic resonance (Mie resonance) increases, resulting in better electromagnetic wave absorption characteristics. Furthermore, when the area ratio is 90% or less, sufficient gaps can be provided between the dielectrics, so that the magnetic resonance phenomenon caused by the electromagnetic waves that penetrate into these gaps can be fully utilized. Therefore, the electromagnetic wave absorption characteristics are excellent. The area ratio may be 10% or more and 75% or less, or may be 10% or more and 50% or less.
[0058] Preferably, the surface density of the dielectrics constituting the dielectric arrangement group is 3 pieces / cm 2 That's all. Here, the number density is the ratio of the total number of dielectrics to the total area of the region on the substrate surface where the dielectrics are distributed. In other words, it is the number of dielectrics per unit area when the electromagnetic wave absorber is viewed from above. By increasing the number surface density, the proportion of dielectrics that cause magnetic resonance (Mie resonance) increases, resulting in better electromagnetic wave absorption characteristics. The number surface density is 15 pieces / cm 2 More than 30 pieces / cm is preferable. 2 The above is more preferable.
[0059] Preferably, the dielectric loss tangent (tan δ) of the dielectrics constituting the dielectric arrangement group is 0.03 or more. By using a dielectric with a high dielectric loss tangent, the magnetic loss during Mie resonance increases and the dielectric loss can also be utilized for electromagnetic wave absorption. Therefore, it is expected that the electromagnetic wave absorption characteristics will be further improved. The dielectric loss tangent may be 0.06 or more, 0.09 or more, or 0.12 or more.
[0060] The electromagnetic wave absorber of the present embodiment includes the dielectric arrangement group that functions as a dielectric metamaterial, and exhibits magnetic loss based on the Mie resonance mode for electromagnetic waves of a specific wavelength. max ; maximum magnetic loss frequency) and effective imaginary part of relative permeability (μ'' ar ) and loss factor (tan δ aM ) has a maximum value. ar The maximum value of the loss factor (tan δ) may be 0.50 or more, 1.00 or more, or 1.50 or more. aM ) may be 0.50 or more, 1.00 or more, 1.50 or more, or 2.00 or more.
[0061] The electromagnetic wave absorber may include other members in addition to the substrate and the dielectric arrangement group. For example, an impedance matching layer or a surface protection layer may be provided on the surface. A reflective member may be provided on the back surface. An example of the impedance matching layer is a layer in which magnetic powder or dielectric powder is dispersed in a resin. An example of the surface protection layer is a layer made of resin or glass. An example of the reflective member is a film-like, foil-like, plate-like, or mesh-like metal member.
[0062] 2. System The system of this embodiment includes an electromagnetic wave radiation source and the above-mentioned electromagnetic wave absorber. In addition, the frequency f (unit: Hz) of the electromagnetic wave radiated by the electromagnetic wave radiation source and the real part ε of the relative dielectric constant of the dielectric of the electromagnetic wave absorber are r ', average diameter D m (unit: μm) and thickness T m (unit: μm) satisfies the following formulas (1) to (4). In the following formulas (1) and (2), c is the speed of light (3.0 × 10 14 μm / sec=3.0×10 8 m / sec).
[0063]
number
number
number
number
[0064] The system of this embodiment includes an electromagnetic wave radiation source and the electromagnetic wave absorber described above. Here, the electromagnetic wave radiation source is a source of leakage (unwanted) electromagnetic wave radiation, such as a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable. An electronic element, an electronic component, or an electronic device including a high-frequency circuit constantly radiates leakage electromagnetic waves from the circuit during operation to the surroundings. In addition, a transmission line or cable transmitting a high-frequency signal radiates leakage electromagnetic waves to the surroundings as the signal is transmitted. A transmitter, an antenna, and a receiver of a radar such as an in-vehicle radar emit a large amount of electromagnetic waves as they operate. By providing an electromagnetic wave absorber, such leakage electromagnetic waves are absorbed, and as a result, electromagnetic interference to the surrounding environment, such as other transmission lines, high-frequency circuits, electronic elements, electronic components, electronic devices, cables, radars, or the human body, can be prevented. Details of the electromagnetic wave absorber are as described above.
[0065] The system of the present embodiment may include a single leakage (unwanted) electromagnetic wave radiation source, or may include multiple radiation sources. The electromagnetic wave absorber may be installed in any manner, as long as it can absorb the leakage electromagnetic wave and prevent electromagnetic interference. For example, the system may be configured with one leakage electromagnetic wave radiation source and an electromagnetic wave absorber provided inside or on the outer surface of the leakage electromagnetic wave radiation source. When the electromagnetic wave absorber is provided inside, it may be provided in a section of an electronic circuit to prevent leakage to other circuits. An electromagnetic wave absorber may be incorporated inside an electronic component to prevent electromagnetic interference between elements included in the electronic component. An electromagnetic wave absorber may be incorporated in a package of an electronic component to prevent electromagnetic interference with other components. An electromagnetic wave absorber may be provided in the housing of an electronic device to prevent electromagnetic interference to other devices or the human body. An electromagnetic wave absorber may be incorporated in an outer coating of a cable to prevent electromagnetic wave leakage. The system of this embodiment can take any form as long as it includes an electromagnetic radiation source and an electromagnetic wave absorber that prevents leakage of electromagnetic waves from the radiation source.
[0066] In addition, the system of this embodiment is configured to calculate the frequency f (unit: Hz) of the electromagnetic wave radiated by the electromagnetic wave radiation source and the real part ε of the relative dielectric constant of the dielectric of the electromagnetic wave absorber. r ', average diameter D m (unit: μm) and thickness T m (unit: μm) satisfies the above formulas (1) to (4). This makes it possible to efficiently absorb electromagnetic waves leaking from electromagnetic wave radiation sources (transmission lines, high-frequency circuits, electronic elements, etc.), thereby making it possible to effectively prevent electromagnetic interference in the surrounding environment.
[0067] To explain this point, as mentioned above, from the results of Fabry-Perot resonance, in Mie resonance, the thickness (T) of the dielectric is half the wavelength of the resonance wavelength (λ R Magnetic loss occurs when the average thickness T of the multiple dielectric bodies provided in the electromagnetic wave absorber is close to msatisfies the above formula (4), magnetic loss based on Mie resonance is induced, and as a result, electromagnetic waves are efficiently absorbed. In the above formula (4), λ' is the wavelength (unit: μm) of the electromagnetic wave in the dielectric. The wavelength in the dielectric is shortened in inverse proportion to the square root of the dielectric constant compared to the wavelength (c / f) of the electromagnetic wave in a vacuum. In addition, in the above formula (4), T m The reason for the wide upper limit of the dielectric constant is the real part ε r This is because the value was measured at 100 MHz. Since the dielectric constant decreases at higher frequencies, this decrease is taken into account. m However, from the viewpoint of suppressing the change in absorption frequency with temperature, it is preferable that the change in the dielectric constant with respect to the frequency is small. In other words, it is preferable that the relationship is close to that of the above formula (9). Therefore, T m It is preferable that the relationship in the following formula (12) is satisfied, it is more preferable that the relationship in the following formula (13) is satisfied, and it is even more preferable that the relationship in the following formula (14) is satisfied.
[0068]
number
number
number
[0069] As described above, by making the diameter of the dielectric smaller than the wavelength of the incident electromagnetic wave, the electromagnetic wave can be efficiently absorbed. Therefore, the average diameter D m The efficiency of electromagnetic wave absorption is improved when the above formula (3) is satisfied. In the above formula (3), λ is the wavelength of electromagnetic wave in a vacuum (unit: μm), which is almost the same as the wavelength in the atmosphere. m It is preferable that the relationship in the following formula (15) is satisfied, it is more preferable that the relationship in the following formula (16) is satisfied, and it is further preferable that the relationship in the following formula (17) is satisfied.
[0070]
number
number
number
[0071] The frequency f of the electromagnetic wave emitted by the electromagnetic wave radiation source is not particularly limited. However, it is preferably 1 GHz or more and 10 THz or less, more preferably 3 GHz or more and 5 THz or less, even more preferably 10 GHz or more and 1 THz or less, particularly preferably 10 GHz or more and 300 GHz or less, and most preferably 30 GHz or more and 100 GHz or less. The frequency f may be 60 GHz or more and 80 GHz or less. The system of this embodiment is provided with the above-mentioned electromagnetic wave absorber, so that leakage (unwanted) electromagnetic waves in the GHz band can be sufficiently absorbed. Specifically, the maximum of electromagnetic wave absorption can be provided within the above-mentioned frequency range, and the absolute value of the return loss at this maximum can be 10 dB or more, 15 dB or more, or 20 dB or more.
[0072] 3. Methods of absorbing electromagnetic waves The electromagnetic wave absorbing method of the present embodiment uses the above-mentioned electromagnetic wave absorber. In addition, the frequency f (unit: Hz) of the electromagnetic wave and the real part ε of the relative dielectric constant of the dielectric of the electromagnetic wave absorber are r ', average diameter D m (unit: μm) and thickness T m (unit: μm) satisfies the following formulas (1) to (4). In the following formulas (1) and (2), c is the speed of light (3.0 × 10 14 μm / sec=3.0×10 8 m / sec).
[0073]
number
number
number
number
[0074] The details of the electromagnetic wave absorption method of this embodiment are as described for the system of this embodiment. That is, the electromagnetic wave is a leakage electromagnetic wave emitted from an electromagnetic wave radiation source such as a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable.
[0075] The frequency f of the electromagnetic wave is not particularly limited. However, it is preferably 1 GHz or more and 10 THz or less, more preferably 3 GHz or more and 5 THz or less, even more preferably 10 GHz or more and 1 THz or less, particularly preferably 10 GHz or more and 300 GHz or less, and most preferably 30 GHz or more and 100 GHz or less. The frequency f may be 60 GHz or more and 80 GHz or less. The method of this embodiment can sufficiently absorb unnecessary electromagnetic waves in the GHz band by using the above-mentioned electromagnetic wave absorber. Specifically, the maximum of electromagnetic wave absorption is provided within the above frequency range, and the absolute value of the return loss at this maximum can be 10 dB or more, 15 dB or more, or 20 dB or more.
[0076] According to the present embodiment, an electromagnetic wave absorber utilizing magnetic loss based on Mie resonance of a dielectric, a system including this electromagnetic wave absorber, and an electromagnetic wave absorbing method using this electromagnetic wave absorber are realized. The electromagnetic wave absorber, the system, and the absorbing method have various advantages.
[0077] Conventional electromagnetic wave absorbers absorb electromagnetic waves by utilizing the dielectric properties of dielectric materials and / or the magnetic properties of magnetic materials. Specifically, they convert electromagnetic wave energy into thermal energy by utilizing the dielectric loss of the dielectric material and the magnetic loss of the magnetic material. In addition, by individually controlling the permittivity of the dielectric material and the magnetic permeability of the magnetic material, the characteristic impedance of the material is matched to the characteristic impedance of the external environment, thereby preventing electromagnetic wave reflection on the absorber surface.
[0078] However, according to the Snoek limit, it is difficult to maintain the high magnetic properties of magnetic materials up to high frequencies. Therefore, conventional materials have limitations in obtaining high absorption properties, especially in the high frequency range above GHz. There is also a known method of attenuating electromagnetic waves by placing a metal plate on the back of an electromagnetic wave absorber to interfere with the reflected waves on the absorber surface, but this method has the problem that the absorption frequency is strongly dependent on the incident angle of the electromagnetic wave.
[0079] In contrast, the electromagnetic wave absorber of this embodiment utilizes magnetic loss based on the Mie resonance of the dielectric, and is not bound by the snake limit because it does not use a ferromagnetic material, and can maintain high absorption performance up to the high frequency range. In addition, since the resonant frequency has a small dependency on the electromagnetic wave incident angle, it has the advantage of being able to handle electromagnetic waves incident from various directions.
[0080] Moreover, the electromagnetic wave absorber of this embodiment includes a plurality of disk-shaped dielectrics. Although not limited thereto, the diameter of the dielectrics is smaller than the wavelength of the incident electromagnetic wave, and the area ratio of the dielectrics is limited to 90% or less. These make the electromagnetic wave absorption characteristics even better. That is, by providing a plurality of dielectrics, gaps are formed between the dielectrics. By reducing the diameter of the dielectrics and arranging the dielectrics so as to be moderately sparse, the electromagnetic waves penetrate into the gaps, and the Mie resonance of the dielectrics is effectively expressed. In contrast, conventional electromagnetic wave absorbers do not utilize Mie resonance. Therefore, an absorbing material is usually arranged on one surface to increase the occupancy rate. That is, unlike this embodiment, the absorbing material is not arranged so as to be moderately sparse.
[0081] The electromagnetic wave absorber, system, and electromagnetic wave absorbing method of the present embodiment, which utilizes magnetic loss based on Mie resonance, are based on a completely unprecedented concept and are epoch-making both academically and industrially. EXAMPLES
[0082] (1) Preparation of electromagnetic wave absorber [Example 1] In Example 1, an electromagnetic wave absorber was produced using a barium titanate (BTO; BaTiO3) sintered body as a dielectric.
[0083] Barium titanate powder with a D50 of 60 nm was used as the dielectric raw material, neopentyl glycol diolate (NOF Corporation, Unistar HP281R) was used as the solvent, and a dispersant (Lubrizol, HPA-N107) was weighed out to obtain the composition shown in Table 1 below, and kneaded using a planetary mixer. A paste was thus produced.
[0084] Next, a metal mask (thickness 150 μm) with multiple circular holes (φ1.2 mm) was placed on an alumina plate, and the prepared paste was applied onto the metal mask. After that, the metal mask was removed, and a paste pattern with a thickness of 150 μm was formed on the alumina. The prepared paste pattern was then fired under the conditions of 1025°C x 3 hours, and multiple barium titanate sintered bodies were obtained as dielectrics.
[0085] 5,200 pieces of the obtained barium titanate sintered bodies were randomly arranged on a polyethylene terephthalate (PET) film (12 cm x 12 cm x 0.05 mm), and epoxy resin was injected into the gaps and cured to produce an electromagnetic wave absorber. The properties of the obtained electromagnetic wave absorber are shown in Table 3 below.
[0086] [Example 2] In Example 2, an electromagnetic wave absorber was produced using a barium titanate (BTO; BaTiO3) sintered body as a dielectric.
[0087] As the dielectric raw material, three types of barium titanate powders with different particle sizes (D50) were used. The dielectric raw material, solvent, and dispersant were weighed out so as to obtain the blending composition shown in Table 1 below. Furthermore, the thickness of the metal mask was changed to 125 μm, and a paste pattern with a thickness of 125 μm was formed. Otherwise, an electromagnetic wave absorber was produced in the same manner as in Example 1.
[0088] [Example 3] In Example 3, an electromagnetic wave absorber was produced using a barium titanate (BTO; BaTiO3) compact as a dielectric.
[0089] A metal mask (thickness 125 μm) with multiple circular holes (φ1.2 mm) was placed on a PET film (12 cm × 12 cm × 0.05 mm), and the paste obtained in Example 2 was applied onto the metal mask. The metal mask was then removed, and a paste pattern with a thickness of 125 μm was formed on the PET film. The obtained paste pattern was dried under reduced pressure at 200 ° C to volatilize and remove a part of the solvent. In this way, 2500 barium titanate molded bodies were produced as dielectrics on the PET. Then, epoxy resin was injected into the gaps between the molded bodies and cured to produce an electromagnetic wave absorber. In Example 3, unlike Example 1, the arrangement of the dielectrics maintains the regular paste pattern of the metal mask and is not randomly arranged.
[0090] [Example 4] In Example 4, barium strontium titanate (BSTO; Ba 0.8 Sr 0.2 An electromagnetic wave absorber was fabricated using TiO3 sintered compact as a dielectric.
[0091] Barium strontium titanate (Ba 0.8 Sr 0.2 First, barium strontium titanate powder was synthesized by solid-state reaction using barium carbonate (BaTiO3), strontium carbonate (SrCO3) and titanium oxide (TiO2). Next, the dielectric raw material, solvent and dispersant were weighed to obtain the composition shown in Table 1 below, and kneaded using a planetary mixer. This produced a paste.
[0092] Next, a metal mask (thickness 100 μm) with multiple circular holes (φ1.2 mm) was placed on an alumina plate, and the prepared paste was applied onto the metal mask. After that, the metal mask was removed, and a paste pattern with a thickness of 100 μm was formed on the alumina. The prepared paste pattern was then fired under conditions of 1200°C x 3 hours, and multiple barium strontium titanate sintered bodies were obtained as dielectrics.
[0093] The obtained barium strontium titanate sintered bodies were randomly arranged on a polyethylene terephthalate (PET) film, and epoxy resin was injected into the gaps between the bodies and cured to produce an electromagnetic wave absorber.
[0094] [Example 5 (Comparative Example)] When applying the paste onto the metal mask, the thickness of the applied paste was randomly changed to form a paste pattern having a thickness of 100 to 200 μm. Otherwise, an electromagnetic wave absorber was produced in the same manner as in Example 1.
[0095] [Example 6 (Comparative Example)] A disk-shaped coating film having a diameter φ of 15 mm and a thickness of 150 μm was formed on the alumina so as to completely fill the absorber. Except for this, an electromagnetic wave absorber was produced in the same manner as in Example 1.
[0096] [Table 1]
[0097] (2) Evaluation For Examples 1 to 6, various characteristics were evaluated as follows.
[0098] <Dimensions of dielectric> For each of Examples 1 to 6, the diameter of the paste pattern was calculated based on the average diameter D mThis is because the shrinkage in the diameter direction after firing is small, so the diameter of the paste pattern can be considered to be the same as the diameter of the sintered body. Regarding the thickness, 20 dielectric bodies were randomly selected from the obtained multiple dielectric bodies (sintered bodies, compacts), and the thickness T i (i=1,2...20) are measured using a laser microscope, and the average value T m Then, the coefficient of variation CV of the thickness was calculated according to the above formulas (10) and (11).
[0099] <Dielectric properties of dielectric materials> The dielectric properties at 100 MHz were measured for the dielectrics obtained in Examples 1 to 6. Specifically, the measurements were performed according to the following procedure. First, a sample was prepared by applying silver paste to both sides of the dielectric to form electrodes. Next, the impedance of the sample was obtained by a voltage-current method, and the obtained impedance was analyzed to obtain the capacitor component and the resistor component. Then, the complex relative dielectric constant (ε r =ε r '-jε r '') was calculated, where ε r ' and ε r '' are the real and imaginary parts of the complex dielectric constant, respectively. The real part of the complex dielectric constant, ε r ' and the imaginary part ε r '' to obtain the dielectric tangent (tanδ E ) was calculated according to the following formula (18).
[0100]
number
[0101] <Characteristics of electromagnetic wave absorbers> For the electromagnetic wave absorbers obtained in Examples 1 to 7, the complex relative permittivity, complex relative permeability, and electromagnetic wave absorption characteristics at 60 to 80 GHz were measured in the following procedure. That is, the reflection characteristics and transmission characteristics of the samples were measured using a vector network analyzer (ME7838A, Anritsu Corporation) by the free space method, and the complex relative permittivity (εar =ε ar '-jε ar '') and complex relative permeability (μ ar =μ ar '-jμ ar '') was calculated, where ε ar and μ ar are the effective complex dielectric constant and effective relative permeability of the entire electromagnetic wave absorber, respectively, and the complex dielectric constant ε r and complex relative permeability μ r It is distinguished from.
[0102] The real part of the relative permeability μ ar ' and the imaginary part μ ar Calculate the frequency dispersion of ar The frequency at which '' has a maximum value is called the maximum magnetic loss frequency f max And f max The real part of relative permeability μ ar '(f max ) and the imaginary part μ ar ''(f max ) to obtain the loss factor tanδ aM (f max ) was calculated according to the following formula (19).
[0103]
number
[0104] A 1mm thick metal plate was placed behind the sample to sufficiently reduce the transmitted components of the electromagnetic wave, and the reflection characteristics were determined. The reflection loss (rate) RL was then calculated from the ratio of the incident wave intensity to the reflected wave intensity. Furthermore, for samples where the reflection loss maximum (absorption maximum) exists within the measurement frequency range, the frequency at which the reflection loss is maximum was determined as the absorption frequency f R Let f R The absolute value of the return loss at the maximum return loss RL R Also, f R Wavelength λ of electromagnetic waves (absorbed electromagnetic waves) in the atmosphere R , and the wavelength λ in the dielectric R' was calculated according to the following equations (20) and (21). In the following equations (20) and (21), c is the speed of light, ε r ' is the real part of the complex dielectric constant of the dielectric at 100 MHz.
[0105]
number
number
[0106] (3) Evaluation results The dielectric structures of Examples 1 to 6 are summarized in Table 2. The frequency characteristics of the dielectric constant, magnetic permeability and transmission attenuation of the electromagnetic wave absorbers of Examples 1 to 6 are shown in Figures 1 to 13. The magnetic properties and absorption properties of the electromagnetic wave absorbers are summarized in Tables 3 and 4.
[0107] [Example 1] As shown in Table 2, the dielectric (sintered body) of Example 1 had an average thickness of 135 μm and a standard deviation of 13 μm. In Example 1, the BaTiO3 content in the raw material paste during dielectric preparation was low. This resulted in a large thickness shrinkage during firing, which is thought to have led to a relatively large standard deviation. Also, as shown in Table 2, the dielectric of Example 1 had a real part of the relative dielectric constant ε at 100 MHz of 135 μm and a standard deviation of 13 μm. r ' was large, about 500. This indicates that the material exhibits a large dielectric response to vacuum.
[0108] The relative dielectric constant of the electromagnetic wave absorber of Example 1 is shown in Figure 1. Since it was produced by dispersing the dielectric (sintered body) in the resin, the dielectric constant was significantly lower than that of the dielectric alone. In addition, no clear resonance behavior was observed in the dielectric constant.
[0109] Figure 2 shows the relative permeability of the electromagnetic wave absorber of Example 1. The real part of the permeability on the low frequency side was nearly 1. The dielectric material contained in the electromagnetic wave absorber does not contain magnetic elements. The value of the real part of the permeability on the low frequency side confirms that ferromagnetic magnetic order based on magnetic elements does not occur. On the other hand, despite the absence of ferromagnetic magnetic order, magnetic resonance occurred near 70 GHz, and the imaginary part of the permeability reached a maximum. The frequency at which the imaginary part of the permeability is maximum (maximum magnetic loss frequency) f max The imaginary part of the relative permeability μ ar '' is 1.53, loss factor (tan δ M ) was extremely large at 1.79 (Table 3). Since no ferromagnetic magnetic order was observed, it is believed that magnetic loss was caused by the Mie resonance mode, which depends on the dielectric constant and thickness of the dielectric.
[0110] The transmission attenuation (absorption characteristics) of the electromagnetic wave absorber of Example 1 is shown in FIG. 8. The transmission attenuation reaches a maximum near 70 GHz, and the peak value at that time is over -10 dB. Mie resonance occurs when the thickness of the dielectric is about half the length of the electromagnetic wave wavelength. However, in the ferroelectric, wavelength shortening occurs due to its dielectric constant, so that the resonance mode occurs in a range where the thickness is sufficiently smaller than the wavelength, as shown in Table 4. The relative dielectric constant of most ferroelectrics in the GHz band is between 100 and 10,000, but in this case, it is considered that the above-mentioned resonance mode occurs by making the thickness of the dielectric about 1 / 20 to 1 / 200 of the measurement wavelength. It is considered that the electromagnetic wave efficiently penetrates and is absorbed in the sintered body near this resonance mode.
[0111] [Example 2] In Example 2, an electromagnetic wave absorber was produced by dispersing a dielectric (sintered body) made of BaTiO3 in a resin, as in Example 1. The BaTiO3 content of the paste was increased by mixing three types of BaTiO3 with different particle sizes (D50) when producing the dielectric. As a result, as shown in Table 2, the difference between the metal mask thickness and the sintered body thickness was 15 μm in Example 1, while it was suppressed to 7 μm in Example 2. A decrease in the coefficient of variation of the thickness, which is thought to be due to a decrease in the shrinkage rate, was also confirmed. In addition, it is thought that the BaTiO3 density in the sintered body is also improved compared to Example 1, and an increase in the dielectric constant of the dielectric (sintered body) was also confirmed as shown in Table 2. As a result, the wavelength shortening effect was stronger in Example 2 compared to Example 1, and the λ R The ratio of ' to dielectric thickness was increased.
[0112] The magnetic permeability of the electromagnetic wave absorber of Example 2 is shown in Figure 3. Although the thickness of the dielectric material of the electromagnetic wave absorber of Example 2 was thinner than that of Example 1, a resonance peak was observed at approximately the same frequency as in Example 1. This is considered to be because the shift to higher frequencies of the resonance mode due to the reduction in the thickness of the dielectric material was almost cancelled out by the shift to lower frequencies of the resonance mode due to the increase in the dielectric constant.
[0113] 9 shows the transmission attenuation (absorption characteristics) of the electromagnetic wave absorber of Example 2. As in the case of magnetic permeability, it was confirmed that the frequency at which absorption was maximized was almost the same as in Example 1.
[0114] [Example 3] In Example 3, a paste was prepared with the same composition as in Example 2, but no firing was performed and only drying was performed to prepare a dielectric (molded body), which was then dispersed in a resin to prepare an electromagnetic wave absorber. The average thickness of the dielectric (molded body) was slightly increased compared to Example 2. This is believed to be due to the presence of some of the solvent and dispersant remaining.
[0115] The magnetic permeability of the electromagnetic wave absorber of Example 3 is shown in Figure 4. The electromagnetic wave absorber of Example 3 has a dielectric made of a molded body, and the same resonant behavior was observed as in the cases of having a dielectric made of a sintered body (Examples 1 and 2). However, the frequency at which resonance occurred shifted slightly to the higher frequency side compared to Example 2. This is thought to be because some of the solvent and dispersant remained, decreasing the dielectric constant of the entire molded body and weakening the wavelength shortening effect.
[0116] The transmission attenuation (absorption characteristics) of the electromagnetic wave absorber of Example 3 is shown in Figure 10. It was confirmed that absorption occurred in the same manner as in the case of using a sintered body (Examples 1 and 2) in response to the magnetic resonance mode. In Example 3, the electromagnetic wave absorber was produced by regularly arranging the dielectrics (molded bodies) in the same manner as the metal mask pattern, but an effect similar to that obtained in the case of random arrangement (Examples 1 and 2) was obtained. This is thought to be because each dielectric has electromagnetic wave absorption ability, and therefore the arrangement of the dielectrics with the surrounding dielectrics has little effect on absorption ability.
[0117] [Example 4] In Example 4, a dielectric (sintered body) was prepared for a composition in which part of Ba in BaTiO3 was replaced with Sr, and this dielectric was dispersed in a resin to prepare an electromagnetic wave absorber. It is known that perovskite-type compounds having this composition exhibit relaxor-like behavior at room temperature. Therefore, the dielectric constant of the dielectric (sintered body) at 100 MHz was higher than that of Examples 1 and 2.
[0118] The magnetic permeability of the electromagnetic wave absorber of Example 4 is shown in Figure 5. Although the thickness of the dielectric was thinner than that of Example 1, resonant behavior was observed at approximately the same frequency. This is thought to be because, with regard to the frequency at which the resonant mode occurs, the effect of shortening the wavelength and reducing the frequency due to the increase in the dielectric constant and the effect of increasing the frequency due to the decrease in the dielectric thickness cancel each other out.
[0119] The transmission attenuation of the electromagnetic wave absorber of Example 4 is shown in Fig. 11. Absorption that is considered to be caused by a magnetic resonance mode was confirmed.
[0120] [Example 5] In Example 5, a dielectric (sintered body) was prepared by preparing a paste with the same composition as in Example 1, and this dielectric was dispersed in a resin to prepare an electromagnetic wave absorber. As shown in Table 2, the average thickness of the dielectric was made almost the same as that of the dielectric in Example 1, while the variation coefficient of the thickness was made very large at about 50%.
[0121] The magnetic permeability of the electromagnetic wave absorber of Example 5 is shown in Figure 6. Compared to Example 1, there was not much change in the frequency of the imaginary part peak, but the peak intensity was significantly weaker. This is thought to be because there was a large variation in the thickness of the sintered body, which caused the resonance frequency of each dielectric to vary, resulting in a smaller magnetic loss at the peak frequency.
[0122] The transmission attenuation of the electromagnetic wave absorber of Example 5 is shown in Fig. 12. Reflecting the behavior of the magnetic permeability, the return loss at the peak frequency was also small.
[0123] [Example 6] In Example 6, a dielectric (sintered body) was prepared from a paste having the same composition as in Example 1, and this dielectric was dispersed in a resin to prepare an electromagnetic wave absorber. As shown in Table 2, the average thickness of the dielectric was almost the same as in Example 1, while the diameter φ was set to 15 mm, which was larger than the measurement wavelength. By increasing the diameter φ, the coefficient of variation of the thickness became smaller, as shown in Table 1.
[0124] The magnetic permeability of the electromagnetic wave absorber of Example 6 is shown in Figure 7. No peak in the imaginary part of the magnetic permeability was observed. This is thought to be because the diameter of the dielectric material is larger than the wavelength, so it no longer functions as a dielectric metamaterial for electromagnetic waves, and magnetic loss based on Mie resonance no longer occurs.
[0125] 13 shows the transmission attenuation of the electromagnetic wave absorber of Example 6. Although some attenuation occurs due to dielectric loss, an effect comparable to that of Examples 1 to 4 was not obtained.
[0126] [Table 2]
[0127]
Table 3
[0128]
Table 4
Claims
1. The dielectric array includes a substrate and a dielectric arrangement group including a plurality of disk-shaped dielectrics. Each of the dielectric bodies constituting the dielectric body arrangement group has a front surface and a bottom surface, and is arranged so that the bottom surface faces one surface of the base body; The dielectrics constituting the dielectric arrangement group have a relative dielectric constant real part ε r ' is 30 or more, and the average diameter D m is 100 μm or more and 10,000 μm or less (0.1 mm or more and 10 mm or less), and the average thickness T m is 20 μm or more and 300 μm or less (0.02 mm or more and 0.3 mm or less), and the average thickness T m Average diameter D m The ratio (D m / T m Ratio) is 3 or more, and the coefficient of variation CV of the thickness T is 20% or less, The maximum value of the loss factor (tan δ aM) is 0.50 or more. An electromagnetic wave absorber that utilizes magnetic loss due to Mie resonance of the dielectric material.
2. 2. The electromagnetic wave absorber according to claim 1, wherein an area ratio of the dielectrics constituting the dielectric arrangement group is 10% or more and 90% or less.
3. The surface density of the dielectrics constituting the dielectric arrangement group is 3 pieces / cm 2 The electromagnetic wave absorber according to claim 1 or 2.
4. 4. The electromagnetic wave absorber according to claim 1, wherein the dielectric tangent (tan δ) of the dielectrics constituting the dielectric arrangement group is 0.03 or more.
5. 5. The electromagnetic wave absorber according to claim 1, wherein the dielectric material is a dried body, a molded body or a sintered body of a dielectric material.
6. An electromagnetic wave absorber described in any one of claims 1 to 5, wherein the dielectrics included in the dielectric arrangement group are arranged regularly or irregularly.
7. A system comprising an electromagnetic radiation source and an electromagnetic wave absorber according to any one of claims 1 to 6, The frequency f (unit: Hz) of the electromagnetic wave radiated by the electromagnetic wave radiation source and the real part ε of the relative dielectric constant of the dielectric r ', the average diameter D m (unit: μm) and the thickness T m (unit: μm) is expressed by the following formulas (1) to (4) (where c is the speed of light (3.0 × 10 14 The system satisfies the above-mentioned standard. [0010] [0025] [0030] [0045]
8. The system of claim 7 , wherein the electromagnetic radiation source is a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable.
9. 9. The system according to claim 7, wherein an absolute value of a return loss of the electromagnetic wave absorber at the frequency f is 10 dB or more.
10. A method for absorbing electromagnetic waves using the electromagnetic wave absorber according to any one of claims 1 to 6, The frequency f of the electromagnetic wave (unit: Hz) and the real part ε of the relative dielectric constant of the dielectric r ', the average diameter D m (unit: μm) and the average thickness T m (unit: μm) is expressed by the following formulas (1) to (4) (where c is the speed of light (3.0 × 10 14 The method satisfies the above requirement. [0050] [006] [0070] [0080]
11. The method according to claim 10 , wherein the electromagnetic wave is a leakage electromagnetic wave from a transmission line, a high-frequency circuit, an electronic element, an electronic component, an electronic device, a radar, and / or a cable.
12. The method according to claim 10 or 11, wherein the absolute value of the return loss of the electromagnetic wave absorber at the frequency f is 10 dB or more.
Citation Information
Patent Citations
Electromagnetic wave absorber
JP2004153135A
Electromagnetic wave shield
JP2011014723A
Electromagnetic wave absorber and method for manufacturing the same
JP2013201359A
Radiowave absorber
JP2013211296A
